Efficacy and safety of PAC‐14028 cream – a novel, topical, nonsteroidal, selective TRPV1 antagonist in patients with mild‐to‐moderate atopic dermatitis: a phase IIb randomized trial. (8th January 2019) - Lee, Y.W.; Won, C.‐H.; Jung, K.; Nam, H.‐J.; Choi, G.; Park, Y.‐H.; Park, M.; Kim, B.
Summary: Background: Transient receptor potential vanilloid subfamily, member 1 (TRPV1) may play an important role in pruritus and inflammation induction in atopic dermatitis (AD). The treatment effect of TRPV1 antagonist via topical application in patients with AD remains unknown. Objectives: To assess the clinical efficacy and safety of PAC‐14028, a TRPV1 antagonist, via topical application in patients with AD. Methods: In this 8‐week, phase IIb, randomized, double‐blind, multicentre, vehicle‐controlled study, patients with mild‐to‐moderate AD were randomized to receive PAC‐14028 cream 0·1%, 0·3%, 1·0% or vehicle cream twice daily. The primary efficacy end point was the Investigator's Global Assessment (IGA) success rate defined as the percentage of patients with an IGA score of 0 or 1 at week 8. The secondary efficacy end points included the severity Scoring of Atopic Dermatitis (SCORAD) index and Eczema Area and Severity Index (EASI) 75/90. Results: A total of 194 patients were enrolled. IGA success rates at week 8 were 14·58% for vehicle cream, 42·55% for PAC‐14028 cream 0·1% ( P = 0·0025 vs. vehicle), 38·30% for PAC‐14028 cream 0·3% ( P = 0·0087 vs. vehicle) and 57·45% for PAC‐14028 cream 1·0% ( P < 0·001 vs. vehicle). In particular, statistically significant differences were found between the vehicle and treatment groups in the IGA success rates with two‐grade improvement. The SCORAD index, EASI 75/90, sleep disturbance score and pruritus visual analogue scale showed a trend towards improvement. No significant safety issues were reported. Conclusions: PAC‐14028 cream may be an effective and safe treatment modality for the treatment of patients with mild‐to‐moderate AD. Abstract : What is already known about this topic? Atopic dermatitis (AD) is one of the most common inflammatory skin diseases characterized by pruritic erythematous skin lesions and barrier dysfunction. Transient receptor potential vanilloid subfamily, member 1 (TRPV1) antagonists suppress the release of pruritic and proinflammatory mediators. The preclinical results demonstrate the feasibility of TRPV1 as a potential therapeutic target for the treatment of AD. What does this study add? TRPV1 regulates inflammation and pruritus in patients with AD. PAC‐14028 cream, a novel TRPV1 antagonist, was superior to vehicle in improving clinical symptoms and signs with a favourable safety profile in adults with mild‐to‐moderate AD. TRPV1 antagonism may play a role as a promising nonsteroidal topical treatment target for AD with a new mechanism of action. Linked Editorial: Song and Armstrong. Br J Dermatol 2019; 180 :971–972 . Plain language summary available online Respond to this article